GEOCHEMICAL FACIES ANALYSIS OF FINE-GRAINED SILICICLASTICS USING TH/U, ZR/RB AND (ZR+RB)/SR RATIOS - Dypvik H.; Harris N.B. (My University, 2001)
Abundance of the trace elements Zr, Rb, Sr, Th and U may provide insight into the sedimentological origin of fine-grained siliciclastic sediments, provided that the units are derived from similar source areas, as demonstrated here with suites of the fine-grained Jurassic and Cretaceous rocks from the Barents Sea and Svalbard. Zr/Rb ratios can be interpreted to indicate grain size variations, while (Zr+Rb)/Sr values reflect variations in the siliciclastic versus carbonate contents. The Th/U ratio can be applied as an indicator of the redox conditions. In 3D plots such as presented here, the interplay between these geochemical factors can be interpreted in terms of the sedimentological evolution of the depositional basin. The geochemical facies analyses show that similar depositional conditions existed on the Jurassic shelf in the two studied localities. The succeeding prodeltaic Cretaceous beds were generally coarser grained and deposited in ventilated depositional conditions.
Keywords: FINE-GRAINED SILICICLASTICS; TRACE ELEMENTS; 3D PLOT; SEDIMENTOLOGICAL EVOLUTION; Cretaceous; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская; Мезозой::Меловая; Mesozoic::Cretaceous